2021
DOI: 10.31674/mjmr.2021.v05i02.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Internet Addiction on Health Anxiety in Malaysian Youth During Covid-19 Pandemic

Abstract: The COVID-19 The pandemic affected the mental health of people. Individuals prefer to collect information from the Internet about the virus, disease, symptoms, reports on statistics, treatments, and any other information related to the pandemic. In this study, we aimed to explore the impact of Internet use in three different levels of users (Internet addicts, over-users, and average-users) on health anxiety during the pandemic among the young population in Malaysia. Four hundred and forty-eight young adult in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A recent study conducted among Malaysian youth during the pandemic which examined the relationship between anxiety and IA, found that individuals with higher internet usage scored more in the anxiety inventory [20]. Therefore, this study aimed to determine the prevalence of internet usage and IG among medical students and whether they are linked to anxiety during the pandemic.…”
Section: Introductionmentioning
confidence: 94%
“…A recent study conducted among Malaysian youth during the pandemic which examined the relationship between anxiety and IA, found that individuals with higher internet usage scored more in the anxiety inventory [20]. Therefore, this study aimed to determine the prevalence of internet usage and IG among medical students and whether they are linked to anxiety during the pandemic.…”
Section: Introductionmentioning
confidence: 94%
“…Work and learning are conducted online, creating another issue: internet addiction to health anxiety. In the recent study by Khodabakhsh et al, four hundred and forty-eight young adults were surveyed (Khodabakhsh et al, 2021). The study showed that high internet use is associated with health anxiety.…”
Section: Impactmentioning
confidence: 99%
“…Most young adults view the Internet as an essential learning, work, and social connection tool, to name a few. The Internet, when coupled with social media, has various benefits that range widely from online education, speedy communication, and online shopping, to accessing online information and professionals in the field of health and medical care (Khodabakhsh, Ramasamy, Tan, & Chan, 2021).…”
Section: Relationship Between Social Media Use and Mental Health Of University Studentsmentioning
confidence: 99%
“…However, exacerbated feedback may arise, in which the return of health anxiety and the perceived reassurance will eventually worsen the initial anxiety, causing a negative cognition should bodily sensations recur or if uncertainties surface with respect to medical test results. This postulate claims that even people with moderate anxiety have the tendency to more frequently seek health-related information online than those without anxiety, but the information deficit may cause health-related worries, and seeking information may also exaggerate the anxious feelings, especially among individuals with cognitive distortion (Khodabakhsh, Ramasamy, Tan, & Chan, 2021).…”
Section: Relationship Between Social Media Use and Mental Health Of University Studentsmentioning
confidence: 99%
See 1 more Smart Citation